Public abstract sculpture in the park: from abundance to environmental importance / Ramlan Abdullah - Abdullah, Ramlan (College of Built Environment, 2023)
This project aims to develop a public sculpture made of wood, the formation of which will be stylized after the form of a four-legged animal.